THE GENERAL GEOLOGY OF THE MERU- CHEPOR AREA WITH EMPHASIS ON QUARTZ VEIN RESOURCE - KEE , CA SSY (Universiti Teknologi PETRONAS, 2014)
Chepor area is known for quartz quarrying as there is a number of operating quartz quarry in that particular area yet there were no detailed geology described by any geologist which the existing geological map is too big to be focus on the particular area. Thus, this paper have drawn a focus on the understanding concerning general geology of Chepor area as there is lack of research papers being published on this area. A detailed geological map of scale of 1:40000 have been constructed. Quartz has been a significant resource in the manufacture and construction field. In this study, rock aggregate test will be carried out to determine the suitability of the quartz for construction use. The rock aggregate test including Water absorption, Flakiness Index, Soundness of Aggregate (5 cycles sodium sulphate solution), Soundness of Aggregate (5 cycles with magnesium sulphate solution), Aggregate Impact Value , Ten Percent Fine value, Aggregate Crushing Value and Los Angeles Abrasion Value. Results showed that coarse-grained granite formed the Kledang Range to the west and adjoining to the granite is a quartz dyke. Alluvium or tailing sand with limestone bedrock is present to the east. Laboratory tests conducted on the quartz dyke showed that the rock aggregate test are not within the aggregate limits set by J.K.R. and cannot be used for construction purposes. The quartz dyke have SiO2 content of 98.7% and are suitable for making colorless, green, window ,amber, sheet, rolled and polished glassware Lastly, proposed a potential quartz quarry based on the suitability of the quartz sample and its commercial usage.